Killer style : how fashion has injured, maimed, & murdered through history - McMahon, Serah-Marie; Matthews David, Alison (Owlkids Books, 2019)
Explores the history of fashion trends that killed or maimed, such as lead-based makeup, mercury-poisoning in hatters, corsets, and flammable flannel. Includes illustrations, sidebars, sources for further learning, and an index.